2014
DOI: 10.1111/ajr.12114
|View full text |Cite
|
Sign up to set email alerts
|

Falls in rural and remote community dwelling older adults: A review of the literature

Abstract: Few studies explored falls and their prevention in rural and remote Australia. The limited literature on the topic suggests that a change in focus to one that utilises existing services and resources will be required to create sustainable outcomes. Four areas are proposed for concentrated effort to reduce the impact of fall-related injury in rural and remote Australia: integration and collaboration among health professionals, promotion of physical activity across the lifespan, community involvement and ownersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 30 publications
1
23
1
1
Order By: Relevance
“…We did not find a statistical difference in the fall rate over the previous year between urban and rural areas, which is in line with other studies. A 2014 study of Australians over 50 years found no difference in fall hospitalizations, fall mortality, or fall-related injuries between city and rural participants [11]. However, we found that lifetime fall history was higher in rural areas, perhaps because the average age of our rural participants was higher than of urban participants.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…We did not find a statistical difference in the fall rate over the previous year between urban and rural areas, which is in line with other studies. A 2014 study of Australians over 50 years found no difference in fall hospitalizations, fall mortality, or fall-related injuries between city and rural participants [11]. However, we found that lifetime fall history was higher in rural areas, perhaps because the average age of our rural participants was higher than of urban participants.…”
Section: Discussioncontrasting
confidence: 67%
“…To date, most falling research has focused on urban residents. Falling incidence and cost in rural elderly populations have been studied but separately from urban populations [11][12], thus, there have been no studies comparing fall characteristics, such as frequency, cause, time, and shoes worn, between urban and rural areas. This study compared fall characteristics between urban and rural areas using data from a large-scale survey conducted in Korea, and presents basic information for establishing fall-related policies for the elderly.…”
mentioning
confidence: 99%
“…An all-field search was conducted between March and May 2014 by using the search terms with a date limit of 31 December 2013. Consistent with other literature reviews, the search strategies used differed on the basis of the database functionality (see the table in the online data supplement) 19 …”
Section: Methodsmentioning
confidence: 99%
“…Jatuh adalah salah satu masalah kesehatan yang sering terjadi pada lansia 65 tahun ke atas (20). Di beberapa Negara didapatkan data, 28-35% lansia orang berusia 65 tahun ke atas atau lansia yang berusia 70 tahun mengalami kejadian jatuh sekitar 32-42% setiap tahun, dan 40% dari orang-orang tersebut dilaporkan mengalami kejadian jatuh yang berulang (21).…”
Section: Jatuh Pada Lansiaunclassified